Overview of HIV, Syphilis and Hepatitis B Screening for Pregnant Women at the Selemadeg Community Health Center, Tabanan Regency, 2019-2021 - Luh Gede Erawati; Made Widhi Gunapria Darmapatni; I Nyoman Wirata; Gusti Ayu Marhaeni (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
Transmission of HIV, Syphilis, and Hepatitis B from mother to child is a vertical transmission. Transmission occurs during pregnancy, during childbirth and during breastfeeding. A strategy is needed to prevent the transmission of HIV, Syphilis and Hepatitis B from mother to child. To overcome this, the government makes PMTCT policy in an effort to eliminate the transmission of triple elimination. The purpose of the study was to determine the description screening of HIV, Syphilis and Hepatitis B in pregnant women at the Selemadeg Health Center. This type of research is descriptive. The research was conducted at the Selemadeg Health Center in May 2022. The type of secondary data, the instrument of collection with data collection sheets. The characteristics of pregnant women are 82.1% aged 20-35 years, 53.1% working mothers, 50.8% have high school education, 49.3% have one child. The results of the screening in pregnant women are one person (0.2%) HIV reactive, six persons (1%) Syphilis reactive, and two persons (0.3%) Hepatitis B reactive.Â  Pregnant women with HIV reactive results are 100% in the age group 20-35 years,100% housewife,100% high school education, and 100% primipara. Syphilis reactive results are 83.3%, in the age group 20-35 years, housewife (66,7%), high school education (66.7%) and multipara (66.7%). Hepatitis B reactive results are 50% in the age gruop 20-35 years, 50 % in the age group > 35 years, 50%, 50% housewife, 50% working mom, 50% high school education 50% and overall multipara. For primary health center to optimize health promotions regarding Prevention of Mother to Child Transmission (PMTCT) at the Selemadeg Health Center.